DIGITAL TRANSFORMATION OF SUSTAINABILITY REPORTING how digital technologies are reshaping... sustainability accounting, data, and disclosure. - Abhayawansa, Subhash (ROUTLEDGE, 2026)
As global sustainability expectations intensify, digital technologies (DTs) are becoming essential tools for efficiently and effectively managing, measuring, and communicating sustainability performance and impact. This book unpacks how emerging and established DTs, from artificial intelligence and blockchain to cloud platforms and the Internet of Things, can transform sustainability reporting and data management, enhance decisionmaking, and improve accountability across value chains.Drawing on insights from extensive interviews and crosssectional surveys of sustainability, accounting, auditing, data science and technology professionals, this book delivers a practical and evidencebased roadmap of how DTs are being leveraged and could be better leveraged in internal and external sustainability reportingrelated activities. It explores how DTs can enhance the efficiency and effectiveness of collecting, analysing, and assuring sustainabilityrelated data, while also supporting scenario planning, target setting, and improving the accessibility and usability of disclosures for stakeholders. This book further examines the key drivers, opportunities, and challenges shaping the use of DTs in sustainability reporting and offers a valuable reference for practitioners and finance professionals through a concise mapping of relevant digital tools and platforms. It also explores the evolving roles and competencies required of accounting and finance professionals to effectively contribute to sustainability reporting and lead technologyenabled sustainability performance.This is a mustread for: Sustainability managers and leaders seeking more efficient, credible, and futureready sustainability reporting practices Policymakers and regulators navigating the digitalisation of corporate transparency and compliance Technology providers aiming to align product innovation with the fastevolving needs of sustainability reporting Educators and students in accounting, finance, sustainability, and data science fields preparing for the future of sustainabilitydriven business Researchers exploring the intersection of digital innovation, regulatory change, and reporting of sustainability risks, performance, and impacts
Keywords: Sustainable development reporting.; Technological innovations.; elektronické knihy; electronic books